Elimination of Large Bladder Stone-Obstructing Pelvic Canal in African Spurred Tortoise (Centrochelys sulcata) with Per-Cloacal Bladder Stone Removal Method without Utilizing an Endoscope - Rickyawan, drh., M.Sc., Nofan; Vivi Oktavia; Dodik Prasetyo (Media Kedokteran Hewan, 2025)
Bladder stone formation in reptiles arises from the accumulation and subsequent solidification of uric acid in the urinary bladder. The bladder stones vary in size and can migrate from the bladder to the pelvic canal. In cases where larger bladder stones enter the pelvic canal, they pose a risk of obstructing the digestive and urinary tracts of the tortoise. This study discusses managing bladder stone elimination in sulcata tortoises (Centrochelys sulcata) located in the pelvic canal without utilizing an endoscope. In 2023, four sulcata tortoises were presented at the Teaching Veterinary Hospital Universitas Brawijaya with diagnoses of large bladder stone-blocking pelvic canals that had been causing digestive and urinary tract obstruction. All of the tortoises have similar clinical signs, such as lethargy, anorexia, inability to defecate, and anuria. Physical examinations and radiography revealed the presence of bladder stones in the pelvic canal, exceeding the dimensions of the pelvic outlet and hindering passage through the cloaca. Treatment involved per-cloacal bladder stone removal. This procedure begins by anesthetizing the sulcata tortoise using ketamine and medetomidine combination, followed by fragmentation and extraction of the bladder stones from the pelvic canal through the cloaca. All procedures were performed without utilizing an endoscope. The success of the treatment was evidenced by radiographic examination, confirming the absence of bladder stones in the pelvic canal, and the recovery of normal defecation, urination, appetite, and activity levels.